Program I am valuable to improve social skills in secondary education students of the Carlos Wiesse Chao school 2023 - Grados Cruz, Paul Miki (2025)
Our research study "I am valuable program to improve social skills in secondary education students of the Carlos Wiesse Chao 2023 school". Our work is based on a systematic review that aims to optimize the most relevant social skills to enhance basic social skills, advanced social skills and enhance social skills in relation to feelings. The creation of this program aims to improve social skills in secondary school students. The methodology is based on a systematic review, taking into account the principles established for the improvement and development of review work by the PRISMA declaration. The study strategy was given by the selection of scientific articles between the years 2018 to 2023, a search of scientific articles indexed in electronic databases was carried out, 20 articles were analyzed, of which 15 scientific articles were selected for said study. It is concluded that social skills are reflected in different situations of daily life and, therefore, can be influenced both positively and negatively.